Euro Area Policies : 2011 Article IV Consultation-Lessons from the European Financial Stability Framework Exercise; and Selected Issues Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
The European Union's (EU) financial stability framework is being markedly strengthened. This is taking place on the heels of a severe financial crisis owing to weaknesses in the banking system interrelated with sovereign difficulties in the euro area periphery. Important progress has been made in designing an institutional framework to secure microeconomic and macroprudential supervision at the EU level, but this new set-up faces a number of challenges. Developments regarding the financial stability may assist in the continuing evolution of the European financial stability architecture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet